Motivating Students In Speaking English Through Small Group Discussion - Nasir, Vebiyanti; Muhamad, Sariwati (Peneliti.net, 2024)
The purpose of this study is to find out whether small group discussion can motivate students in speaking English or not and to know the factors of students have not motivation in speaking English. The participants of the researcher are 25 students of tenth grade of MA Al-Khairaat Guraping. The method of the research is qualitative research and the result of the research is the students were motivated when small group discussion applied as a technique in teaching English. The students were so happy and active when speaking English in small group and they can speak without afraid they will make mistake, they can responds the teacher’s questions and asking a questions when they did not know the materials and they have desire in practice speaking and they know the important of English for their future. They also can work together in a group, they can practice speaking without afraid and feeling shame, and the extensive materials make them happy to learn English. So that, the conclusion is small group discussion can motivate students’ in speaking English but the teacher must have big attention to the students who still less in motivation.